Proximat Composition of By-product of Indonesian Ongole Crossbreed Cattle - Edy Susanto; A. Fadlilah; M.F Amin; Wahyuni; Dyanovita Alkurnia; Alfian Adi Atma; Wenny Ladhunka; Arif Arya; Lestariningsih (Jurnal Ternak, 2025)
Ongole crossbreed cattle (OCC) is a type of local cattle in Indonesia. Exploration of the main products of local livestock, especially by product, of local Indonesian cattle has never been carried out. The important potential of the by-product is to combat protein malnutrition and food insecurity in many countries. The aim of the study was to explore the proximate composition. The research was carried out using the exploratory laboratory method by taking objects in the field and then analyzing them in the laboratory. Samples were taken from the Animal Slaughterhouse of Lamongan district which originated from 8 Farmers. The variables observed were proximate includes water content, protein, carbohydrate, fat and ash. The proximate composition was dominated by water and protein content with the highest average value obtained from the red offal species. Differences in proximate composition also occur between male OCC and female OCC.